Cross sections for the reactions e+e− → K0SK0L, K0SK0Lπ+π−, K0SK0Sπ+π−, and K0SK0SK+K− from events with initial-state radiation - Lees, Jean-Pierre; Adametz, Aleksandra; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2014)
We study the processes e+e−→K0SK0Lγ, K0SK0Lπ+π−γ, K0SK0Sπ+π−γ, and K0SK0SK+K−γ, where the photon is radiated from the initial state, providing cross section measurements for the hadronic states over a continuum of center-of-mass energies. The results are based on 469 fb−1 of data collected with the BABAR detector at SLAC. We observe the ϕ(1020) resonance in the K0SK0L final state and measure the product of its electronic width and branching fraction with about 3% uncertainty. We present a measurement of the e+e−→K0SK0L cross section in the energy range from 1.06 to 2.2 GeV and observe the production of a resonance at 1.67 GeV. We present the first measurements of the e+e−→K0SK0Lπ+π−, K0SK0Sπ+π−, and K0SK0SK+K− cross sections and study the intermediate resonance structures. We obtain the first observations of J/ψ decay to the K0SK0Lπ+π−, K0SK0Sπ+π−, and K0SK0SK+K− final states.
Gesehen am 14.10.2020
Im Titel sind die Pluszeichen und Minuszeichen hochgestellt